Descriptive study of possible relation between cardio-ankle vascular index and lipids in hypertension subjects - Jinbo Liu; Huan Liu; Hongwei Zhao; Na Zhao; Hongyu Wang (Open Exploration Publishing Inc., 2024)
Aim: The cardio-ankle vascular index (CAVI) is a new evaluation indicator for arteriosclerosis. This study investigated the relationship between the CAVI and lipid levels in patients with hypertension in a real clinical environment. Methods: This descriptive study enrolled 2,656 patients (male/female: 1,016/1,640) from the Outpatient Department of Vascular Medicine of Peking University Shougang Hospital and Jinding Street Community Health Service Center. CAVI was measured using a VaseraVS-1000 vascular screening system (Fukuda Denshi, Tokyo, Japan). Results: Age, body mass index (BMI), waist circumference, hip circumference, CAVI, systolic blood pressure (SBP), diastolic blood pressure (DBP), creatinine, fasting plasma glucose (FPG), uric acid (UA), hypersensitive C-reactive protein (hs-CRP), homocysteine, HbA1c, and triglyceride (TG) were significantly higher in the hypertension group than in the non-hypertension group. The levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were significantly lower in the hypertension group than in the non-hypertension group. The CAVI value was significantly higher in patients with hypertriglyceridemia and normal LDL-C than in those with normal TG and hyper-LDL-C. Age, waist circumference, UA, FPG, HDL-C, hs-CRP, HbA1c, BMI, SBP, and DBP were independently associated with CAVI in all patients. Beta blockers were negatively correlated with CAVI (β = -0.411, P = 0.011). Sex (male) and history of hypertension and diabetes mellitus were positively correlated with CAVI (β = 0.419, P < 0.001; β = 0.247, P = 0.011; β = 0.638, P < 0.001; respectively). Conclusions: The CAVI was significantly higher in patients with hypertension and exhibited differences based on sex. Although we did not find a significant correlation between CAVI and TG, it remains crucial to maintain blood pressure to prevent the development of arteriosclerosis.